o resultado da expressão (2412:12-8)-1³ +(48-6×2)
Soluções para a tarefa
Respondido por
13
(2412 : 12 -8) -1³ + (48 -6 × 2) =
201 -8 - 1 + (48 - 12 ) =
201 -8 -1 +48 -12 =
201 +48 -8 -1 -12 =
249 -21 =
228
201 -8 - 1 + (48 - 12 ) =
201 -8 -1 +48 -12 =
201 +48 -8 -1 -12 =
249 -21 =
228
lelunardi1:
: )
Respondido por
10
(2412: 12 -8) -1 + (48-6x2) =
(201 -8) -1 +(48-12) =
193 -1 + 36 = 228
espero ter ajudado!!
(201 -8) -1 +(48-12) =
193 -1 + 36 = 228
espero ter ajudado!!
Perguntas interessantes
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Biologia,
1 ano atrás
História,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás